Embedded and IoT Devices Firmware Security - Cong Doan Dinh (Journal of Technical Education Science, 2025)
The Internet of Things (IoT) has gone a long way since its inception. However, the standardization process in IoT systems for IoT safety solutions is still in its early stages. Lots of studies have been conducted on its quality evaluation to address threats to IoT across different layers. However, most current works have failed to take into their consideration of the security aspects of the firmware in the IoT ecosystem. The lack of a comprehensive survey on IoT firmware security aims to highlight the important reasons for a firmware insecurity in IoT, list vulnerabilities, and perform an in-depth review of the key analysis techniques. Such rapid development has made IoT and embedded systems become interesting targets for potential attackers, especially the firmware attacks. This Article hereby presents some information related to the device firmware as started by highlighting the importance of the firmware security, classifying the vulnerabilities in IoT, the processes of analyzing the firmware vulnerabilities through some Open source tools, and as illustrated by analyzing some firmwares of the popular devices.